Plant attractants and rewards for pollinators: their significance to successful crop pollination - Zariman, Nur Athirah; Omar, Nurul Alia; Abdul, Nurul Huda (International Society of Academicians, 2022)
Plant and pollination have a mutualistic relationship where both parties offer and gain benefits for each other. The plant pollinator interactions resulted in successful crop pollination in which the plant received pollination services by animal pollinator to increase food production that eventually increase crop economic value. Overall, ecosystem is highly dependent on pollinator thus there is a need to review potential valuation method of crop production and analyse the current understanding of the value of pollination service towards the ecosystem as well as the traits plant offer and benefits that pollinator gain from the relationship. The attractant and rewards highly depending on each other. Plant often able to attract pollinators through traits like the shape, size and colours of flower, deception, scents as well as location. In the meantime, plant would provide a reward for pollinators that visited the flower which includes food from pollen and nectar that contains high nutritional value, energetic rewards to reduce energy cost of survival, protection and shelter against predator and not to forget breeding, oviposition and mating sites inside the flower plant. This review emphasizes the ecological relationship of plant and pollinator that resulting in effective crop pollination if the attractant and incentives are significantly reliant on one another. However, there could be flaws, such as modifications to plant or environmental factors, would affect the rewards supplied and resulting in decrease crop output. With this review and current technological advancements, optimistically deeper investigations in the interaction of pollinator and flowering plant can be conducted and best pollinator management approaches can be established to secure sustainable crops production.